Academic and Career Outcomes Following Sexual Assault in Early Adulthood: A Comparison of LGBQ+ and Heterosexual Women - Moschella-Smith, Elizabeth A. (Violence against women, 2023)
Young adults (aged 18–24) who identify as lesbian, gay, bisexual, or queer (LGBQ+) report high rates of sexual assault (SA) victimization, yet much of the research on adverse outcomes resulting from SA has overlooked LGBQ+ victims. A probability-based sample of 901 adults was recruited to examine the negative academic and career outcomes attributed to SA during early adulthood among LGBQ+ cisgender women. LGBQ+ women were more likely to report negative impacts on academic and career goals (e.g., changed course of study) and transitions (e.g., switched jobs) following SA victimization than heterosexual women. Implications for research and LGBQ+ services are discussed.